Plasma lactate levels and lactate clearance as predictors of outcome in patients with sepsis and septic shock - Patil, Rashmi; S., Chikkanarasareddy P.; K., Mallesh (International Journal of Contemporary Pediatrics, 2020)
Background: Severe sepsis and septic shock are the major causes of admission and deaths in the ICU, killing one in four (and often more) and increasing in incidence. In order to improve the clinical outcomes in these patients, it is crucial to obtain early recognition of patients who are at risk of death and to optimize the clinical decision making in a timely manner. In order to monitor the metabolic consequences of shock and hemodynamic management, plasma lactate levels can be used in critical illness. Objective of the study is to estimate plasma lactate and lactate clearance in sepsis and septic shock patients and to correlate plasma lactate and lactate clearance as predictors of mortality. Methods: This study is a prospective observational study conducted over 18months. Children with age of 1 month to 18 years admitted to the Paediatric intensive care unit with sepsis and septic shock were enrolled in the study. ABG at admission to document plasma lactate and lactate repeated at 6 and 24 hrs. Lactate clearance calculated at 6 and 24 hrs. The final outcome in terms of survival or death will be recorded. Results: Majority of the children fall in the class between 1-6 months 51(48.11%). Male comprises 69(65.09%). Among these, Sepsis 36(33.96%); followed by Pneumonia 34(32.07%). Survivors group were 35(33.02%) and non-survivor was 71(66.98%). The Non survivor group was observed to have lower mean values of lactate clearance and found to be statistically significant. Specificity of Lactate clearance was 63.52% and Sensitivity 76.02% respectively. The results were positively associated with lactate level at 24 hours found to be significant effect of survivability when compared to non-survivor. Conclusions: Lactate clearance is vital and markable sign for screening of septic shock at early stage for therapeutic option. Further, 24-hours lactate estimation (cut off values) clearance appears superior to 6 h lactate clearance in predicting mortality in such patients.